Evaluation of pharmacist-led telemedicine medication management for hypertension established patients during COVID-19 pandemic: A pilot study - Li, Xiaoye; Hu, Jialu; Yao, Yao; Zuo, Chengchun; Wang, Zi; Li, Xiaoyu; Lv, Qianzhou (Frontiers in Public Health, 2022)
AIM: To evaluate the impact of a telemedicine medication management service in patients with hypertension. METHODS: Participants were allocated to either a telemedicine service (N= 173) or usual care (UC) (N=179). The primary outcome was blood pressure (BP) reduction from baseline to the 6-month follow-up visit, the proportion of the target BP achievement, overall adherence to prescribed medication as well as a composite of non-fatal stroke, non-fatal myocardial infarction and cardiovascular death. RESULTS: At 6 months, BP was controlled in 89.6% (n=155) of intervention patients and 78.8% (n=141) of UC patients (OR=1.14, 95% CI=1.04-1.25, P=0.006), giving a mean difference of -6.0 mmHg (-13.0 to -2.5 mmHg) and -2.0mmHg (-4.0 to -0.1 mmHg) in SBP and DBP, respectively. 17.9% (n=31) of the patients in the intervention group were non-adherent with medications, compared with 29.1% (n=52) in the UC group (P=0.014). The composite clinical endpoints were reached by 2.9% in the intervention group and 4.5% in the control group with no significant differences (OR=1.566, 95% CI=0.528-4.646). CONCLUSIONS: Telemedicine medication management for hypertension management had led to better blood pressure control and medication adherence improvement than UC during COVID-19 epidemic, resulting in a reduction of overall adverse cardiovascular events occurrence.